High prevalence of anxiety, depression, and stress among remote learning students during the COVID-19 pandemic: Evidence from a meta-analysis - Xu, Tianyuan; Wang, Huang (Frontiers in Psychology, 2023)
The COVID-19 pandemic significantly influenced all aspects, and an estimated of 1.5 billion students across the globe have been forced to keep up with online courses at home. Many recent empirical studies have reported the prevalence of students’ mental health problems caused by remote learning during the COVID-19 pandemic, but few studies have aggregated these results. Therefore, to strengthen statistical power, the paper aims to examine the prevalence of anxiety, depression and stress among remote learning students during the COVID-19 pandemic via meta-analysis. A total of 36 original articles have been selected from 5 academic databases, including Web of Science, PubMed, Scopus, EBSCO and Google Scholar, covering 78674 participants in 19 nations, and yielding 60 effect sizes (22 for anxiety, 17 for depression and 21 for stress) based on the random effected model via Comprehensive Meta-Analysis (CMA) software. The result showed that the prevalence of anxiety, depression and stress among remote learning students during the COVID-19 pandemic was as high as 58%, 50% and 71%, respectively. Besides, moderator analysis found that: (1) the prevalence of anxiety and depression among students in higher education was significantly higher than that of students in elementary education; (2) More medical students and students in emergency remote learning contexts suffer from mental stress than their non-medical and traditional distance learning counterparts. Thus, the COVID-19 pandemic triggers concerns related to physical health and mental disorders, especially for remote online learning students. The current situation should be brought to the forefront by educators to develop psychological interventions for relieving students’ anxiety, depression and stress during the pandemic period.